African and American Selves: « Contact Zones » in All Our Names by Dinaw Mengestu - Duboin, Corinne (Études littéraires africaines, 2017)
Ethiopian American writer Dinaw Mengestu’s third novel All Our Names (2014) is a double narrative that alternates between post-independence Uganda and post-Civil Rights America, thus offering a critique on both postcolonial Africa and multiracial America. It gives voice to both an African student who seeks refuge in the U.S. and to an American social worker, a white Midwesterner deep-rooted in her hometown. This essay examines how Mengestu constructs his two characters and weaves together their painful singular stories as parallel subjective first-person narratives that offer two different perspectives on Africanness and Blackness. It further analyzes how he uses their encounter (a secret interracial love affair) to point to the contrasts and similarities of their two separate worlds and thus expose the instability of identity and the sense of self that go beyond their differences and affect both characters.